(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This study explores the integration of Artificial Intelligence (AI), particularly Natural Language Processing (NLP), into the field of Qur’anic exegesis (tafsir), focusing on mapping the contextual meanings of key concepts across the Qur’anic text. By analyzing terms such as ʿadl (justice), raḥma (mercy), and ʿilm (knowledge), this research employs AI-driven models to trace their semantic variations and contextual usage across different surahs and themes. The study utilizes a library research method supported by computational techniques like root-word extraction, semantic clustering, and thematic mapping, revealing patterns consistent with classical interpretations while also highlighting new possibilities. Findings indicate that AI can enhance thematic analysis and intertextual exploration in tafsir, though it requires theological oversight to ensure hermeneutical integrity. The research concludes that AI, when applied responsibly and collaboratively, can serve as a powerful complementary tool to traditional tafsir, enriching our understanding of the Qur’an in the digital age.